Glomerulopatia em cão com hemoparasitose - Lucena, Rivaldo Bruno Medeiros de (Universidade Federal Rural do Semi-Árido, 2017)
This report describes as activities carried out during the Mandatory Supervised Internship, no Veterinary Hospital Jerônimo Dix-Huit Rosado Maia, Federal Rural Semiarid University, Campus Mossoró / RN, in the period of June 2017, totaling 240 The objective of improving the knowledge acquired during the course of veterinary medicine correlating with as practical activities in the medical practice area of small animals. All cases followed during the stage include the case of a 5-year-old unrecorded dog (SRD), weighing 15.3 kg with glomerulonephritis triggered by hemoparasitosis. The same arrived at the veterinary hospital (HOVET) to carry out consultation for his general condition. Blood samples were collected for hemogram and serum biochemistry. After receiving the examinations to observed that the animal had hemoparasitosis and mild anemia, as well as, azotemia. Thus, the patient was asked to undergo ultrasonographic examination. Being, observed renal. Therefore, with all these findings the patient is diagnosed with glomerulopathy and hemoparasitosis. In this way the therapy was prescribed for the same one that consisted in the elimination of the hemoparasitosis and the control of the damages of the glomerulopathy. For this reason, it is possible to conclude that the supervised stage has a fundamental role in the training of the veterinary medicine consumer, since through it it is possible to improve the theoretical knowledge, correlating them with a practice.
Relatório
Keywords: Cão; Hemoparasitose; Glomerulopatia; Dog; Hemoparasitosis; Glomerulopathy; CIENCIAS AGRARIAS::MEDICINA VETERINARIA